DEVELOPMENT OF GEOMETRY MOBILE LEARNING TO ENHANCE STUDENTS' MATHEMATICS LEARNING INTEREST - Muliyana, Ana; Panjaitan, Adi Wibowo; Simatupang, Frengki (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
The development research aims to produce a mobile learning application for geometry to enhance students' interest in learning mathematics. The product encompasses solid geometry materials for 7th-grade junior high school students. The development process follows the ADDIE model: Analyze, Design, Development, Implementation, and Evaluation. The product underwent testing with 7th-grade students at a junior high school in Yogyakarta. Data collection instruments included a questionnaire on students' interest in learning mathematics, a product validation sheet, teacher and student assessment sheets, and an observation sheet on the feasibility of the learning process. These instruments were utilized to measure the validity, effectiveness, and practicality of the developed product. The research findings indicate that: (1) The developed mobile learning application for geometry is presented using Creative Problem Solving syntax, complemented with features such as liveworksheets, Geogebra, instructional videos, Quizizz, and Google Forms, facilitating the enhancement of mathematical creativity. (2) The developed product is declared valid based on the validation results obtained from two media experts and two content experts, with an average Aiken index reaching 0.94 out of the maximum score of 1, categorizing it as "High." The product is assessed as practical based on teacher assessment at 96.55%, student assessment at 71.28%, and an average learning process implementation percentage of 85.83%. The product is also deemed effective due to a significant increase in the variable of students' interest in learning mathematics. Thus, the developed geometry mobile learning application meets the criteria of validity, practicality, and effectiveness.